Long-Lasting Trajectory of Population Ageing in Lithuania: Fundamental and Specific Factors - Stankūnienė, Vladislava (Lithuanian Journal of Statistics, 2017)
The article analyses the population ageing of Lithuania for almost a hundred years. The aim of the article is to evaluate the trends of population ageing of Lithuania and to analyse the preconditions and factors of the ageing trajectory fluctuation. Based on demographic development theories and methodological insights in the estimation of influence of different factors on the ageing trends, the fundamental and specific changes in the ageing of Lithuanian population are evaluated. The analysis relies on the official information of Lithuania and international population databases.
Keywords: population ageing; age structure; median age; mean age; Lithuania